IMPLEMENTASI TEKNOLOGI INFORMASI DALAM MANAJEMEN KONSTRUKSI BANGUNAN BERKELANJUTAN - Maret Jerman Samosir (Kohesi: Jurnal Sains dan Teknologi, 2025)
In today’s modern er, so much technology is scattered everywhere, even today’s life is inseparable from information technolog. The use of information technologycan help reduce the time to process data and communication information information. Construction digitalization makes it easier for project manajers to carry out their duties, including planning, implementing and supervisingprojects more effectively. By using, digitalinformation technologytoday, it can accelarate project completion and reduce manual errors and optimize project power. Technology plays a major role in achieving sustainable construction goals. With the continued develoment of technology, the construction sector can take advantage of innovations to reduce environmental impacts, increaseenergy efficiency and optimize the use of natural resources